THE EFFECT OF USING CARD GAMES ON VOCABULARY LEARNING ACHIEVEMENT OF THE FIRST YEAR STUDENTS OF SMPN 5 TAPUNG - Mila Federika Fiantina; Effendy Gultom; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research is aimed to find out whether there is a significant effect of using Card Games vocabulary learning achievement of the first year students of SMPN 5 Tapung. The problem to be discussed here is as follows: Is there a significant effect of using card games on vocabulary learning achievement of the first year students of SMPN 5 Tapung. This research is one group pretest-posttest design. Total sampling technique is used to get the sample. 53 students in class VII-A and class VII-B are taken as the sample. The results of the data analysis shows that the mean scores of the pre-test and the post-test is 62.11 and 74.94. In other words, the mean score of the post-test is higher than the pre-test. The result also shows that the value of t-test (12.83) is higher than t-table (2.007) at the significance level 5%. Therefore, alternative hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. It can be concluded that there is a significant effect of using card games on vocabulary learning achievement of the first year students of SMPN 5 Tapung.Keywords: Card Games, Vocabulary, Learning Achievement.